Analysis of Variance and Surface Response Temperature Interaction on Adsorption Behaviour of Copper in Alkaline Medium - Ubogu, Augustine E.; Fayomi, Ojo S.I; Atiba, Joshua. O (International Journal of Integrated Engineering, 2026)
Copper's susceptibility to chloride-induced deterioration has increased research interest in sustainable corrosion inhibitors. Using electrochemical techniques (potentiodynamic polarisation, open-circuit potential) at temperatures (30–60°C) and concentrations (0.2–0.8 g), this study investigates fishbone ash as a green inhibitor for copper in 0.5 M NaCl. At 30°C/0.8g, the results show mixed-type inhibition behaviour with an efficiency of 98.6% (corrosion rate reduction: 195.96 to 2.69 ?m/yr). Temkin adsorption study showed physisorption dominance (?G°ads = -10.47 to -12.23 kJ/mol) and high surface interaction (Kads = 1.1475–1.4931 mol?¹). optimum performance was found at 53.37°C with 0.49g inhibitor through statistical optimisation using response surface methods, resulting in a predicted corrosion rate of 1.59 ?m/yr (99.3% reduction compared to control). With optimal conditions allowing for >98% corrosion suppression, these results confirm fishbone ash's efficacy as an environmentally beneficial inhibitor.